Is enzyme immobilization a mature discipline? Some critical considerations to capitalize on the benefits of immobilization - Bolivar, Juan M; Woodley, John M; Fernandez-Lafuente, Roberto (Chemical Society reviews, 2022)
Enzyme immobilization has been developing since the 1960s and although many industrial biocatalytic processes use the technology to improve enzyme performance, still today we are far from full exploitation of the field. One clear reason is that many evaluate immobilization based on only a few experiments that are not always well-designed. In contrast to many other reviews on the subject, here we highlight the pitfalls of using incorrectly designed immobilization protocols and explain why in many cases sub-optimal results are obtained. We also describe solutions to overcome these challenges and come to the conclusion that recent developments in material science, bioprocess engineering and protein science continue to open new opportunities for the future. In this way, enzyme immobilization, far from being a mature discipline, remains as a subject of high interest and where intense research is still necessary to take full advantage of the possibilities. Enzyme immobilization has been developing since the 1960s and although many industrial biocatalytic processes use the technology to improve enzyme performance, still today we are far from full exploitation of the field.